2017
DOI: 10.1007/s12015-017-9719-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cell Seeding Density and Inflammatory Cytokines on Adipose Tissue-Derived Stem Cells: an in Vitro Study

Abstract: Adipose tissue-derived stem cells (ASCs) are known to be able to promote repair of injured tissue via paracrine factors. However, the effect of cell density and inflammatory cytokines on the paracrine ability of ASCs remains largely unknown. To investigate these effects, ASCs were cultured in 8000 cells/cm2, 20,000 cells/cm2, 50,000 cells/cm2, and 400,000 cells/cm2 with and without 10 or 20 ng/ml tumor necrosis factor alpha (TNFα) and 25 or 50 ng/ml interferon gamma (IFNγ). ASC-sheets formed at 400,000 cells/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…In contrast, we discovered unchanged gene expression levels of FGF2, TNF-α, and IL-6 in hASCs cultured on type 3 NFC dressing compared with control cells when using the higher cell density. Sukho et al have shown that cell seeding density affects greatly to the cytokine and growth factor secretion levels of hASCs [49]. Further, Fig.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In contrast, we discovered unchanged gene expression levels of FGF2, TNF-α, and IL-6 in hASCs cultured on type 3 NFC dressing compared with control cells when using the higher cell density. Sukho et al have shown that cell seeding density affects greatly to the cytokine and growth factor secretion levels of hASCs [49]. Further, Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Type 3 NFC dressing did not induce any remarkable cytotoxicity [46], and hASCs adhered to the surface of type 3 NFC dressing within 24 h and showed similar morphology compared with the control cells after 1-week culturing. However, the used cell density was excessively higher compared with the traditionally used cell densities that have been identified to affect the growth and functionality of cells [47][48][49]. In specific, high cell density has been shown to promote paracrine action of hASCs [49], which might benefit the wound repair process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, in contrast to other studies, IV administration of BMSCs did not show any effects in terms of kidney function based on serum Cr and blood urea nitrogen. Since paracrine effects of MSCs depend on the number of cells , therapeutic effects are expected to be stronger when the number of transplanted cells increase. However, at the same time, mortality increases due to pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because cell culture density is known to have a substantial effect on experimental outcome owing to paracrine signaling 28 , we tested the effect of altering cell concentrations of ISEMFs and ECs. We investigated four different loading cell densities, each sequential density being double to the one prior ( Fig.…”
Section: Isemf and Ec-derived Vasculature Is Quantitatively Responsivmentioning
confidence: 99%